Prevalence and factors associated with chronic wounds in older adults in primary care - Chrystiany Plácido de Brito Vieira; Telma Maria Evangelista de Araújo (SciELO, 2018)
ABSTRACT Objective: To analyze the prevalence of pressure injuries, diabetic and vasculogenic ulcers and associated factors in older adults attended in primary care. Method: A cross-sectional, analytical study with older adults attended in the Family Health Strategy in a Brazilian municipality. Data collection was performed from January to March 2016 using interviews and evaluations of injuries. The variables were submitted to the multivariate logistic regression model using the odds ratio, with their respective 95% confidence intervals and significance set at <0.05. Results: 339 older adults participated in the study. The mean age was 71.1 years, 67.3% were female, 44% were illiterate, 85% had low family income, 91.7% had underlying diseases, 37.2% had dietary restrictions, and 76.1% did not practice physical activity. The prevalence of pressure injury was 5.0%, diabetic ulcer 3.2%, and vasculogenic ulcer 2.9%. Not working and not regularly practicing physical activity increased the chances of presenting these injuries by 1.5 and 2.3 times, respectively. Being actively mobility and not having dietary restrictions were protective factors for not developing chronic wounds. Conclusion: The prevalence of injuries among older adults was high, and its occurrence is associated with socioeconomic and clinical characteristics.